2001
DOI: 10.1088/0741-3335/43/8/302
|View full text |Cite
|
Sign up to set email alerts
|

Edge characteristics and global confinement of electron cyclotron resonance heated plasmas in the TJ-II Stellarator

Abstract: The edge parameters of electron cyclotron resonance heated plasmas in the TJ-II stellarator are reported. Data from atomic beam diagnostics and electrical probes have been used for edge and scrape-off layer characterization. Scans in heating power and plasma density for H and He plasmas have been performed, for a given magnetic configuration. A linear increase of the diffusion coefficient at the last-closed magnetic surface with the ratio of injected power to plasma density and a similar value of that paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…The values obtained are very close to those obtained experimentally in Ref. [38] in which the particle confinement time was found to be approximately τ P ≈ 10 5 × (P in /n e ) −1.7 ms, where P in is the ECRH injected power in kW and n e the line integrated density in 10 19 m −3 . They are also in agreement with a predictive transport code [39] using the plasma profiles, absolutely calibrated H α signals and EIRENE code simulations to estimate flux surface averaged particle sources [40].…”
Section: Resultssupporting
confidence: 89%
“…The values obtained are very close to those obtained experimentally in Ref. [38] in which the particle confinement time was found to be approximately τ P ≈ 10 5 × (P in /n e ) −1.7 ms, where P in is the ECRH injected power in kW and n e the line integrated density in 10 19 m −3 . They are also in agreement with a predictive transport code [39] using the plasma profiles, absolutely calibrated H α signals and EIRENE code simulations to estimate flux surface averaged particle sources [40].…”
Section: Resultssupporting
confidence: 89%
“…Transition to an improved confinement regime has been observed in TJ-II for some ECRH plasma conditions [19], [20]. In agreement with this result, it has been shown that the development of sheared flows at the plasma edge of the TJ-II requires a critical value of plasma density or density gradient that depends on global plasma parameters [9], [10], [21], [22].…”
Section: Confinement Transitions In Tj-ii Ecrh Plasmasmentioning
confidence: 56%
“…The application of a few dry discharges was required for recovery, but this was only transiently obtained. A second factor in play was the presence of the Enhanced Particle Confinement (EPC) mode, characterized by a sudden increase of particle confinement at a critical density in the order of 0.6 Â 10 19 m À3 [10]. Transition into this mode was found to strongly depend on fuelling pulse shape and amplitude [11] and, its development can be eventually suppressed by proper tailoring of the gas puffing.…”
Section: Wall Conditioning Of the Tj-ii Stellaratormentioning
confidence: 99%